Encapsulation of turmeric extract and rice bran oil in alginate hydrogel microcapsules - Hanan, A. M. Ali (Food Technology Research Journal, 2024)
Turmeric extract (TAE) and rice bran oil (RBO) have grown in popularity among consumers in recent years due to their wide spectrum of biological activity. The main bioactive component of turmeric, curcumin, has demonstrated promise as a possible anti-carcinogenic agent. Meanwhile, RBO rich in γ-oryzanol and other phytosterols, has demonstrated efficacy in enhancing immune system function, thereby shielding the body against diseases. Microencapsulation has the ability to conceal the distinct taste and smell of oil and to shield bioactive substances from the environmental elements. Alginate hydrogels possess several outstanding characteristics, including hydrophilicity, biodegradability, biocompatibility, and non-toxicity, that make them suitable for enveloping bioactive food components. The objective of this study was to obtain and characterize alginate microcapsules containing turmeric aqueous extract and rice bran oil and to evaluate the effect of freeze drying and air drying on curcumin; γ-Oryzanol; total phenols contents and DPPH of TAE and RBO microcapsules. Chemical and sensory evaluation showed that Non-dried and freeze-dried microcapsules were significantly accepted.